Estudo ergonômico na linha de montagem de tratores agrícolas - Costa Neto, Wilson Valente da (2008)
This work reports a case study undertaken on the assembly line of a Brazilian tractor manufacturer. Work conditions were analyzed from an ergonomic point of view, to identify irregularities that might jeopardize production or the health of employees. The layout of the workstations is in fixed position, all steps of the assembly are taken in the same place, once positioned the tractor is not moved until finished. The assembly line worker possessed a high level of freedom when performing his activities, being allowed to move around, and have work breaks, with no limitations as to movements or excessive repetitions. However, the greatest worry was toward the efforts and postures undertaken by the workers, therefore the NIOSH and REBA methods were used. The results were alarming, with an IL>2.5 and REBA action level of 3 (ergonomic risk) what indicates the imminent need of ergonomic intervention. When medical history and interview answers were analyzed, no complains of pain could be associated with the workers activity in the company. The lack of pain complaints related to the irregularities identified in the work place may be associated with the short time of activities the workers have in the company. From these conclusions, a reform needs and implementation costs survey was carried out.